Review of the book “Redes técnicas e urbanas no centro-norte brasileiro” - Revista Geografares, Editor (Geografares, 2025)
Review of the book "Redes técnicas e urbanas no centro-norte brasileiro", edited by Denis Castilho, Kelly Bessa, Fernando Oliveira, and Dallys Dantas.
Keywords: urban infrastructure; urban network; regional planning; Brazil